Polonisation Policy of the Polish Government against the Lithuanian National Minority (1935–1939) - Ereminas, Gintautas (Genocidas ir rezistencija, 2015)
The subject of the article is the Polish government’s targeted policy of Polishisation in the Vilnius region in 1935–1939. Based on the materials of the Lithuanian educational society Rytas, the aim is to show how and under what difficult conditions the Society’s teachers and employees worked for the sake of the Lithuanian culture.